2015
DOI: 10.1007/s00187-015-0226-x
|View full text |Cite
|
Sign up to set email alerts
|

Strategy implementation through hierarchical couplings in a management control package: an explorative case study

Abstract: We examine how couplings of management control (MC) elements help to implement an organization's strategy. Despite prior research stating that couplings between MC elements form a fruitful soil for further research, empirical studies in this area are still scarce. We draw on coupling theory to explore three hierarchical relations between MC elements, and examine how these couplings help to implement the organization's strategy. We conducted a single case study in a medium-sized Dutch municipality, using interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 28 publications
2
25
0
1
Order By: Relevance
“…We know that action control is less applicable to uncertainty and change, as well as requiring strong management skills (Haustein et al 2014). Earlier research has also indicated that personnel control may work differently for different organizations (Kolk and Schokker 2016) and that the more complex an organization is, the more different and specific controls are needed (Haustein et al 2014;Otley 1994). Gazelle companies in the early stages of becoming a larger organization with a complex structure may still be more strongly oriented by personnel control tied to operations and aligned with the corporate strategy, future mission, and goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know that action control is less applicable to uncertainty and change, as well as requiring strong management skills (Haustein et al 2014). Earlier research has also indicated that personnel control may work differently for different organizations (Kolk and Schokker 2016) and that the more complex an organization is, the more different and specific controls are needed (Haustein et al 2014;Otley 1994). Gazelle companies in the early stages of becoming a larger organization with a complex structure may still be more strongly oriented by personnel control tied to operations and aligned with the corporate strategy, future mission, and goals.…”
Section: Discussionmentioning
confidence: 99%
“…They viewed behavioral controls as those systems and mechanisms that include processes and techniques embedded in a formal organizational context and are designed to increase the probability that individuals will attain the organizational goals accordingly (Chenhall 2003;Flamholtz et al 1985). Management (Malmi and Brown 2008) and organizational control (Flamholtz et al 1985) is thus a theory of performance goals and, specifically, how performance goals can be reached (Ghalayini and Noble 1996;Guenther 2013;Kolk and Schokker 2016). While an organizational goal is more tuned towards accomplishment of organizational goals, management control seems conceptually to veer more towards the achievement of overall strategic goals.…”
Section: Behavioral Theories In Accounting and Management Controlmentioning
confidence: 99%
“…For Van der Kolk and Schokker [127], the control of management are all the guarantees that directors must give to ensure that the behavior of the employees is consistent with the objectives and strategies of the organization; this definition is built based on what is said in [128,129]. In FSP, the different manager hierarchy and the management control system (MCS) have a considerable influence.…”
Section: Formulation Of Strategiesmentioning
confidence: 99%
“…vii Undtagelser er dog van der Hengel et al (2014), der studerer 12 hollandske kommuner og finder, at økonomistyringssystemer ofte er løst koblet mellem de hierarkiske niveauer. Van der Kolk and Schokker (2016) finder i et studie af en enkelt hollandsk kommune, at kommuneplaner og afdelingsplaner er taet koblet. Endvidere viser , hvordan den hierarkiske kobling af budgetprocesser ogteknikker forstaerkes, når budgetlaegningen er et centralt planlaegningsredskab.…”
Section: Det Nye Samarbejdes Potentiale Prøves Afunclassified